2010
DOI: 10.1007/s11277-010-0079-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Maximum Ratio Transmission for Downlink OFDMA Relay-based Networks

Abstract: In this paper, a novel and practical transmission scheme for a Multiple Input Multiple Output-Orthogonal Frequency Division Multiple Access (MIMO-OFDMA) relaybased network is proposed and evaluated. We coin the term Virtual Maximum Ratio Transmission (VMRT) for the scheme which obtains diversity and array gain at both links in a two-hop transmission, while keeping the complexity low. Besides, the requirements of Channel State Information needed at the different network elements such as the Base Station, Relay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Only user 1 results are presented because similar performance is obtained by the different users, as explained before. In [25], it is shown that we can obtain diversity and array gain on both hops, and this gain increases as the number of RS does. Since this paper is focused on the performance of channel estimation and LDPC codes, we fixed the number of transmit antennas at the BS to 4, the number of relays to 8 (and 8, 16, 32 for LDPC codes), and the number of users to 4.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only user 1 results are presented because similar performance is obtained by the different users, as explained before. In [25], it is shown that we can obtain diversity and array gain on both hops, and this gain increases as the number of RS does. Since this paper is focused on the performance of channel estimation and LDPC codes, we fixed the number of transmit antennas at the BS to 4, the number of relays to 8 (and 8, 16, 32 for LDPC codes), and the number of users to 4.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…(4) All RSs receive this value from each UT, and according to the minimax BER criterion, the one with the minimum maximum BER is scheduled to transmit. As was shown in [25], this metric is the one which obtains the performance closest to the optimum. If qualities are sorted out in ascending order so that q 1 > q 2 > • • • > q Nu , the UT with q 1 is selected.…”
Section: Virtual Maximum Ratio Transmission (Vmrt)mentioning
confidence: 86%
See 3 more Smart Citations